Fiber laser-microscope system for femtosecond photodisruption of biological samples - Yavaş, Seydi (Optical Society of America, 2012)
We report on the development of a ultrafast fiber laser-microscope system for femtosecond photodisruption of biological targets. A mode-locked Yb-fiber laser oscillator generates few-nJ pulses at 32.7 MHz repetition rate, amplified up to ∼125 nJ at 1030 nm. Following dechirping in a grating compressor, ∼240 fs-long pulses are delivered to the sample through a diffraction-limited microscope, which allows real-time imaging and control. The laser can generate arbitrary pulse patterns, formed by two acousto-optic modulators (AOM) controlled by a custom-developed field-programmable gate array (FPGA) controller. This capability opens the route to fine optimization of the ablation processes and management of thermal effects. Sample position, exposure time and imaging are all computerized. The capability of the system to perform femtosecond photodisruption is demonstrated through experiments on tissue and individual cells.